A high resolution record of late quaternary climatic and environmental change in Taranaki, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Earth Science at Massey University, Palmerston North, New Zealand - Tinkler, Robert John (Massey University, 2013)
A high-resolution characterisation of climatic and environmental change in Taranaki, New Zealand over the last 80,000 years using biotic and abiotic proxies is presented. This research contributes to the small set of sediment cores that extend from the present back through the Last Glacial Maximum (LGM) in the southern North Island, and adds to the small number of near-continuous cores in New Zealand. Fossil pollen data presented here provides a record of vegetation changes in response to climate change (temperature, wind and rainfall). In addition, the project applies a recently developed pollen temperature transfer function (Wilmshurst et al. 2007) to quantify, for the first time, temperature change across the entire LGM in this region, and elucidates the timing of Late Quaternary New Zealand climatic events and phases. Climate change timing and magnitude is tested against the climate event stratigraphy (CES) developed by the NZ-INTIMATE (INTegration of Icecore, Marine and Terrestrial archives) group (Alloway et al. 2007), including: Last Glacial Coldest Period (LGCP); the mid-eLGM Interstadial; the Last Glacial-Interglacial Transition (LGIT); Termination I; the Antarctic Cold Reversal (ACR); the Late-Glacial Warm Period (LGWP), the Late-Glacial Reversal (LGR); and Early Holocene Warming (EHW). During the Moerangi Interstadial between 40,000 and 30,000 cal yrs BP, both the Eltham and coastal Taranaki pollen records show that cold-climate taxa such as Nothofagus menziesii, Nothofagus subg. Fuscospora, Hoheria, Plagianthus, Phyllocladus and Poaceae dominated the pollen assemblage. In addition to being cold, low numbers of fern and tree fern spores imply that conditions were drier than present. The LGCP at Eltham (29,000 – 18,000 cal yrs BP) began around 1,200 years earlier than similar records from elsewhere in New Zealand. Transfer functions suggest that mean annual temperatures at the LGCP/ LGM at Eltham were 5.7°C cooler than present. Within the LGCP, the mid-eLGM Interstadial described in similar records from New Zealand seems to be evident in the W-MAT-derived temperature curve at Eltham, where warming of around 0.8°C occurs between 27,000 and 24,500 cal yrs BP. The LGIT appears to have begun around 18,000 cal yrs BP and concluded around 14,600 cal yrs BP at Eltham, which agrees well with speleothem data from Northwest Nelson, but is more short-lived than at Otamangakau Bog where the LGIT is thought to have persisted for another 1,500 years. A period of sharp cooling inferred from the Eltham pollen record between 16,600 and 15,000 cal yrs BP, when mean annual temperature fell between 1°C and 4°C from the previous period, is matched in time, but not in intensity at some other western and central North Island, and some South island sites, and may be a sampling artefact. The LGWP duration at Eltham (14,600 – 13,500 cal yrs BP) broadly corresponds with NZ-INTIMATE and Northwest Nelson estimates of 14,800 – 13,500 cal yrs BP; mean annual temperatures at Eltham came within 0.6°C of modern-day mean annual temperatures at this time. The timing of the LGR at Eltham shows good agreement with NZ-INTIMATE estimates (Alloway et al. 2007; Lowe et al. 2008), that is, from around 13,500 to 12,500 cal yrs BP. The LGR onset at Eltham preceded onset at the Auckland maars by 600 years and concluded 1,500 years earlier than at Auckland; mean annual temperature at Eltham at this time was approximately 2°C cooler than the present day MAT of 11.2°C. The EHW event commenced at Eltham around 12,500 cal yrs BP, around 1,000 years earlier than at Kaipo Bog, Otamangakau Bog; and largely synchronous with the Auckland maars and Okarito. Pollen records from coastal Taranaki sites span d18O Stage 5a (Otamangakau Interstadial, c. 80,000 yrs BP) through to d18O Stage 2 (Last Glacial-Interglacial Transition, c. 18,500 cal yrs BP), and encompass the stadial complex between these two interstadials (d18O Stage 4, c. 70,000 – 60,000 yrs BP). These records contribute to the small number of pollen-based paleoenvironmental and paleoclimatic narratives for New Zealand extending from the LGIT to the Otamangakau Stadial (d18O stage 5a) time periods. A major contribution of the current A High Resolution Record of Late Quaternary Climatic and Environmental Change in Taranaki, New Zealand study is to reconstruct and characterise d18O stage 5a and d18O stage 4 temperatures based on two pollen transfer functions developed by Wilmshurst et al. (2007). During d18O Stage 5a around 80,000 cal yrs BP, conditions were warmer and wetter than the succeeding glacial. d18O Stage 4 and the early part of d18O Stage 3 were cool with relatively low precipitation and were likely to have been windy at coastal Taranaki sites. Although d18O Stage 4 was cool, it was not as cold as the LGM: pollen transfer functions showed decreases in estimated mean annual temperature from d18O stage 5a, with mean annual temperatures falling around 2°C to reach 7°C. Precipitation likely decreased during d18O stage 4, as indicated by low levels of drought-intolerant taxa Dacrydium cupressinum, Cyathea smithii, and monolete spores, whilst low shrub diversity implies that disturbance was likely to have been low. During early d18O stage 3, the climate warmed and became wetter in coastal Taranaki, as indicated by increasing conifer abundance; in particular Dacrydium cupressinum, high abundance of Cyathea smithii, and a decline in cold-tolerant Nothofagus, Halocarpus, Asteraceae, and Poaceae after 60,000 yrs BP. These conditions persisted for < 5,000 years before temperatures decreased again, then between 50,000 and 40,000 yrs BP the decline in Poaceae and cold-tolerant shrubs Phyllocladus, Halocarpus and Asteraceae, as well as the sharp rise in tall tree conifers, all point to climate amelioration. Conditions were still relatively cool; although pollen transfer functions imply that that mean annual temperatures increased slightly, with mean annual temperature estimates fluctuating between 7°C and 8°C, this was approximately 3 to 4°C cooler than present. For the first time in New Zealand, aerosolic quartz dust was extracted from organic sediments; this peat-derived data informs a paleowind narrative for Taranaki. The technique used in the current study to extract quartz from peats can be considered successful, insofar as relatively pure samples of quartz could be isolated in sufficient mass to be able to measure them, and relate the data to the age model and the coeval pollen influx. The paleowind reconstructions from Eltham can be summarised as follows: strong winds dominated between 36,200 and 35,100 cal yrs BP, 30,746 and 32,101 cal yrs BP, 28,364 to 17,477 cal yrs BP, and 16,118 to 15,806 cal yrs BP. Intermediate winds occurred between 30,746 and 28,364 cal yrs BP, 17,477 and 16,118 cal yrs BP, and 15,619 to 14,916 cal yrs BP; winds of light intensity dominated between 34,777 and 32,101 cal yrs BP and 14,916 and 9,900 cal yrs BP. Major dust peaks at 31,358 cal yrs BP; 21,300 cal yrs BP and 15,955 cal yrs BP all correlated well with the Vostok ice core as well as marine core P69 (Stewart & Neall 1984), and Onaero and Waitui in northern Taranaki. Similarly, dust minima after about 15,000 cal yrs BP at Eltham, Vostok, marine core P69, Onaero, and Waitui suggests that the quartz dust signature at Eltham is consistent with both global and regional estimates of dust influx as the atmospheric dust load responded to changes in wind direction and strength, in particular the intensity of westerly winds, and changes to sediment source area characteristics such as vegetation cover. Combining fossil pollen data and aerosolic quartz dust results is a new technique to investigate the relationship between wind intensity, temperature and plant assemblages. The Eltham fossil pollen and aerosolic quartz data was analysed to determine how the relative proportions of competitive, stress tolerant and ruderal taxa respond to winds of differing intensities over time, as well as quantifying the impact of wind of different intensities on plant diversity over the period 36,200 to 9,900 cal yrs BP. In essence, competitor, C-selected taxa increased in relative abundance, and stress-tolerant, S-selected and ruderal, r-selected taxa decreased over the last 15,000 years at Eltham, as both temperature and wind intensity ameliorated. Wind data was examined against pollen diversity data to test the Intermediate Disturbance Hypothesis (IDH) in the vegetation of the Taranaki region. A moderate relationship between floral diversity and dust flux was found, with periods of high and low dust flux corresponding to lower diversity, and periods of intermediate dust flux corresponding to higher diversity, as predicted by the IDH.
Keywords: Palynology; Paleoclimatology; Paleobotany; Paleoclimatology; Paleobotany; Late Quaternary; Taranaki; New Zealand